Developing Algorithms of Ternary Grid Technique for Optimizing Expert System’s Knowledge Base - Yuliadi Erdani (Jurusan Teknik Informatika, Fakultas Teknologi Industri, Universitas Islam Indonesia, 2006)
The quality and the error possibility of knowledge in the expert system’s knowledge base depend directly on the knowledge acquisition process from the expert. Knowledge acquisition is therefore still the most difficult and error-prone task for knowledge engineer while building an expert system. The Ternary Grid technique has potentiality to achieve the above mentioned performance. It is a new technique for knowledge elicitation/acquisition. The Ternary Grid knowledge acquisition is convenient for improving the knowledge performance.To realize the concepts and to bring its influences into the knowledge base optimization, some algorithms of the Ternary Grid technique have been developed. This paper describes the optimization process of knowledge base and the development process of mentioned algorithms.Keywords: technic, intelligence systems, expert system, knowledge acquisition